Factors Determining the Willingness of Nigerian Clinicians to Recommend Protected Oral Sex: An Online Exploratory Study - Kehinde Kazeem Kanmodi; Jacob Njideka Nwafor; Ugochukwu Anthony Eze; Babatunde Abiodun Amoo; Afeez Abolarinwa Salami; Bello Almu; Mike Eghosa Ogbeide; Precious Ehi Obute; Timothy Aladelusi; Oladimeji Adebayo; Lawrence Achilles Nnyanzi (MDPI AG, 2022)
Oral sex, a risky sexual behaviour, is now a common sexual behaviour in Nigeria. Nigerian clinicians play crucial roles in the promotion of healthy sexual behaviours among the lay public. This study seeks to identify those factors that determine the willingness of Nigerian clinicians to recommend protected oral sex to patients with history of oral sex practice. This study surveyed 330 clinicians in Nigeria, using an e-questionnaire circulated via WhatsApp and Telegram. The collected data were analysed using SPSS version 21 software. The majority (89.1%) of the respondents were willing to recommend protected oral sex for patients engaging in oral sex. Amidst all of the factors (sociodemographic factors, sexual history, etc.) investigated, only one factor (which was the uncertainty about the risk level of oral sex) was found to predict the willingness to recommend protective measures to patients on oral sex (OR = 3.06, p = 0.036). In conclusion, only few factors were found to influence Nigerian clinicians in engaging in patient education on safer oral sex practices.